Graphyne as a promising substrate for the noble-metal single-atom catalysts. (December 2015) - Ma, D.W.; Li, Tingxian; Wang, Qinggao; Yang, Gui; He, Chaozheng; Ma, Benyuan; Lu, Zhansheng
Abstract: Based on first-principles calculations, the potential of graphyne as substrate materials for noble-metal (Au, Pt, Ir, Pd, Rh, and Ru) single-atom catalysts have been systematically investigated. It is found that the adsorption of most considered noble-metal single atoms is very strong at the hollow site above the center of the acetylenic ring of the graphyne sheet and their diffusion away from this site towards its neighboring sites is rather difficult, which makes it highly possible to realize well-ordered and uniformly distributed noble-metal single-atom catalysts on graphyne. Furthermore, the catalytic activity of the Ru-decorated graphyne was investigated by using CO oxidation as a probe. The calculated low energy barrier for the reaction suggests that the Ru-decorated graphyne is a viable catalyst for CO oxidation at low temperature. Based on electronic structure analyses, the high catalytic activity of this system is attributed to the charge transfer and the orbital hybridization between the adsorbates and the Ru atom. This study suggests that graphyne sheets are promising substrates for the synthesis of the noble-metal single-atom catalysts.